Animal welfare in halal studies: trends and insights from bibliometric analysis - Safitri, Lis; Syamsi, Afduha Nurus; Cahyo, Danang Nur; Muatip, Krismiwati (Universitas Airlangga, 2025)
This study aims to describe the publication trend in the SCOPUS database concerning animal welfare in halal studies from 2004 to 2024. This study employed a bibliometric analysis approach with the Biblioshiny application and VOSviewer for data visualisation. The results of the study indicated that a significant increase in animal welfare-related research in halal studies occurred in 2014, while the documents that received the most citations were published in 2008. The United Kingdom is the leading nation in publishing documents on animal welfare in halal studies in total; however, the institution with the highest document output is Universiti Putra Malaysia. The results of the keyword co-occurrence analysis revealed that the study clusters can be grouped by animal type: small ruminants, big ruminants, and poultry slaughter. Regarding thematic evolution, studies on stunning and comparisons between halal slaughter and other religious slaughter remain basic themes in the 2004-2014 or 2015-2024 time slices. Niche themes in the first period revolve around biotechnology, food sustainability, and other areas aimed at producing meat fit for consumption. Meanwhile, niche themes in the second period contain animal welfare studies on social media. Bibliographic coupling resulted in clusters on animal welfare and meat quality; a halal supply chain focused on animal welfare; the examination of halal standards across different nations; the application of slaughtering techniques regarding their effectiveness; the implementation of animal welfare in abattoirs; and the prohibited stunning technique in slaughter Keywords: Animal Welfare, Halal, Evolution, Trend, Bibliometric